قياس مخاطر الائتمان المصرفي ودورها في تحقيق الافصاح المحاسبي بالمصارف العراقية: أطار مقترح (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Bank credit  function plays an important role in realizing the targets of commercial banks , so that the credit dominate the most of assets for these banks , also the credit contribute by bigger share of operational income for these banks .Bank credit faceshigh challenge that it is bank credit risks which hinder realizing goals of bank credit . the researcher discover that in spite of the international accounting standards assured that it  is necessary to disclose about risks related assets, which include bank credit, and also disclosure about fund which specified to face probable loss for this credit , but the recent disclosure about bank credit risks and its provision indicate that it faces sever defect which hinder to realizing benefits needed for users of banks statements to recognize real bank credit activity, as well recent credit provision formation needs to develop to be more convenience with credit risks .To face all these criticisms , the researcher suggest a model for measure bank credit risks aiming to develop the accountancy disclosure about this risks and its provision which realize the targets of bank statement users more effectively , and develop the method of credit provision formation to complete more accurately